Does economic globalisation affect income inequality? A meta‐analysis. (9th August 2020) - Heimberger, Philipp
Abstract: A large volume of econometric literature has studied the impact of economic globalisation on income inequality around the world. However, reported econometric estimates vary substantially, which makes it difficult to draw valid conclusions. This paper presents a quantitative summary and analysis of existing estimates regarding the globalisation–inequality relationship. We use a new data set consisting of 1, 254 observations from 123 primary studies. By applying meta‐analysis and meta‐regression methods, we obtain several main findings. First, globalisation has a (small‐to‐moderate) inequality‐increasing effect. Second, while the effect of trade globalisation is small, financial globalisation shows a more sizeable and significantly stronger inequality‐increasing impact. Third, we find an average inequality‐increasing impact of globalisation in both advanced and developing countries. Fourth, education and technology moderate the impact of globalisation on income inequality.